Two new species of subtribe Monoctonina Mackauer from Europe (Hymenoptera, Braconidae, Aphidiinae) - Tomanović, Željko; Petrović, Andjeljko; Kocić, Korana; Čkrkić, Jelisaveta; Casiraghi, Alice; Saval, José M. Michelena (Zootaxa, 2023)
Falciconus hispanicus sp. n. and Monoctonus montenegrinus sp. n. are described as new members of the subtribe Monoctonina from Spain and from high mountain habitats of Montenegro, respectively. The main diagnostic characters of the newly described species and their host plant-host aphid associations are discussed.